Design factors of femur fracture fixation plates made of shape memory alloy based on the Taguchi method by finite element analysis. (24th March 2018) - Ko, Cheolwoong; Yang, Mikyung; Byun, Taemin; Lee, Sang‐Wook
Abstract: This study proposed a way to design femur fracture fixation plates made of shape memory alloy based on computed tomography (CT) images of Korean cadaveric femurs. To this end, 3 major design factors of femur fracture fixation plates (circumference angle, thickness, and inner diameter) were selected based on the contact pressure when a femur fracture fixation plate was applied to a cylinder model using the Taguchi method. Then, the effects of the design factors were analyzed. It was shown that the design factors were statistically significant at a level of p  = 0.05 concerning the inner diameter and the thickness. The factors affecting the contact pressure were inner diameter, thickness, and circumference angle, in that order. Particularly, in the condition of Case 9 (inner diameter 27 mm, thickness 2.4 mm, and circumference angle 270°), the max. average contact pressure was 21.721 MPa, while the min. average contact pressure was 3.118 MPa in Case 10 (inner diameter 29 mm, thickness 2.0 mm, and circumference angle 210°). When the femur fracture fixation plate was applied to the cylinder model, the displacement due to external sliding and pulling forces was analyzed. As a result, the displacement in the sliding condition was at max. 3.75 times greater than that in the pulling condition, which indicated that the cohesion strength between the femur fracture fixation plate and the cylinder model was likely to be greater in the pulling condition. When a human femur model was applied, the max. average contact pressure was 10.76 MPa, which was lower than the yield strength of a human femur (108 MPa). In addition, the analysis of the rib behaviors of the femur fracture fixation plate in relation to the recovery effect of the shape memory alloy showed that the rib behaviors varied depending on the arbitrarily curved shapes of the femur sections. Abstract : Three design factors of femur fracture fixation plate made of shape memory alloy affecting the contact pressure on the bone were selected. The factors most affecting the contact pressure were found inner diameter, thickness, and circumference angle in that order when simulated on a cylindrical bone model by Taguchi method. The max. average contact pressure between the fixation plate and the human femur models was found much low compared to the yield strength of human femurs.